Historical memory in the global digital world: semiotic and rhetorical aspects - Vorobyova, Svetlana V. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The article reveals the semiotic and rhetorical aspects of historical memory, taking into account the challenges of the global digital world. For this, the ontological foundations and epistemological mechanisms of historical memory have identified as its strategic resources. It has substantiated that, firstly, the ontological foundations of historical memory are the ratio of factuality, conventionality (indexation) and symbolism of collective and individual memory. Secondly, that the epistemological mechanisms of historical memory are formed at the intersection of ways of perceiving the world (diachrony and synchrony), and rhetorical schemes of presentation (metaphors) and representation (metonymy). The conceptual model of justification is based on the reconstruction of the ideas of C. Peirce, C. W. Morris, M. Halbwachs, J. A. Barash, P. Nora, J. Rusen, E. Levinas, S. Galabru, E. Mechoulan. The reasons for the vulnerability of the memory of a network individual in the extraterritorial conditions of the global digital world, which impede civic-patriotic self-identification, are indicated: existential gaps in time, cosmopolitanism, traces of history. Ways to overcome memory heterotopia had outlined.